2016
DOI: 10.1021/acs.jced.5b00428
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Interactions of Poly(ethylene oxide) and Ionic Liquid 1-Butyl-3-methyl-imidazolium Bromide by Viscosity and Spectroscopy

Abstract: In this research, the solution of poly­(ethylene oxide) in binary mixtures of water and ionic liquid, 1-butyl-3-methyl imidazolium bromide, were studied via spectroscopic and viscometric at the temperature range of 288.15–313.15 K. Also, the effects of ionic liquid, 1-butyl-3-methyl imidazolium bromide, on the thermodynamic parameters of dilute aqueous solutions of poly­(ethylene oxide), such as polymer–solvent interaction parameter, theta temperature, the heat of dilution parameter, and the entropy of dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It demonstrates that the choice of polar dangling chains such as PEG is critical in the enhancement of ionic mobility. Indeed, the existence of hydrogen bonding between the imidazolium group and PEO has been reported. , This interaction could allow better the dissociation of the 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI) ionic pair by hindering the cation and creating a polar medium to promote the ionic movement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrates that the choice of polar dangling chains such as PEG is critical in the enhancement of ionic mobility. Indeed, the existence of hydrogen bonding between the imidazolium group and PEO has been reported. , This interaction could allow better the dissociation of the 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI) ionic pair by hindering the cation and creating a polar medium to promote the ionic movement.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the existence of hydrogen bonding between the imidazolium group and PEO has been reported. 62,63 This interaction could allow better the dissociation of the 1-ethyl-3methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI) ionic pair by hindering the cation and creating a polar medium to promote the ionic movement. VTF parameters of the synthesized ionoelastomers were extrapolated, with R 2 fit values above 0.99, confirming that the movement of ions was correlated to those of polymer chains.…”
Section: Synthesis Of Ionoelastomer Based On Pilmentioning
confidence: 99%
“…A population of PEO atoms may be located around the long hexyl chain of [HMIM] + under high pressures. The studies of the 1-alkyl-3-methylimidazolium bromide ILs indicate that some hydrogen bonds between the cation and Br - are replaced by hydrogen bonding between the imidazolium and oxygen atom of PEO upon the addition of PEO to the ILs [ 27 , 28 ]. Furthermore, it has been concluded that for the 1-alkyl-3-methylimidazolium ILs, PEO can solvate the large imidazolium moieties with less stringent local modification via the van der Waals interaction with the PEO chains [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The linear polymer PEO is generally water-soluble owing to the presence of the ethylene oxide group, and the oxygen atoms of PEO are promising candidates as hydrogen-bond acceptors (HBAs) [ 20 , 27 , 28 ]. Researchers have shown that some associations between IL cations and anions may be substituted by the interactions of IL cations and PEO oxygen atoms upon mixing PEO with ILs [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation